Utility of Spacing for Third Molar Teeth Along with its Eruption, for Determination of Age of an Individual: A Pilot Study (Medico Legal Update, 2021)
Background: Determination of individuality of person is one of the main objectives in any medico-legalexamination. Age of an individual is one of the key indicators to establish identity. Eruption of third molarteeth is used frequently by forensic experts all over the world for age determination. Spacing for third molaris another known phenomenon and few studies have been done so far to establish its use in age determination.However we did not find any study to seek combined use of spacing for third molar and eruption of all thirdmolar teeth, for age determination.Aims and Objectives: To establish utility of spacing for third molar along with eruption of third molarineach socket for determination of age; and to devise an equation by using these characteristics to determineage.Material and Methodology: Current study is descriptive observational type of a study, conducted on 201consenting individuals of age ranging from 17 to 22 years, after applying inclusion criteria. Oral examinationof individual was done and gathered information was later statistically analyzed using Microsoft excel.Results: Alinear regression equation– BJGMCFMT equation (Y = 0.149 x + 15.57) is devised for agedetermination, by using unique scoring system for parameters like spacing for third molar tooth and itseruption.Conclusion: Combined use of parameters like spacing for third molar and its eruption can be quantitativelyused for age determination with certain amount of accuracy and precision.